PENINGKATAN HASIL BELAJAR KOGNITIF IPA MENGGUNAKAN METODE EKSPERIMEN DI SEKOLAH DASAR” - Marvinda Rizki Dirgantara; Usi Woro Minarsih (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study is to know the magnitude of the increase students' cognitive learning using the experimental methods in the 248 population at class of the Elementary School of 235 Palembang, and the subject number of research of 24 students. The data analsis used is the quantitative and qualitative data compiled from cognitive study tests over two cycles and from testing data collection techniques, interview sheets, observation, documentation and field notes.Research activities carried out during a two-cycle cycle with each cycle are three meetings and are conducted on thematic studies for elementary science materials. Cognitive tests show an increase in coginitf learning on cycle I to cycle ii with a percentage of 78.12% at good criteria to 88.67% showing excellent criteria.Based on the results of learning activities students show 3.28 value to 3.54 with a change of criteria to excellent on the second cycle. Teacher's activity shows 3.26 data with good criteria on cycles I and for cycles II with average value 3.7 is really good criteria. The interviews performed show that teachers have the ease of learning science, after using experimental methods, and the repsons of students studying the abstract concepts in the direction of concrete which is immaterial in excellent practice.The weakness that appears is indicated in students' activities in compiling the learning observation report. Based on the learning activities that take place it could be concluded that effective experimental methods can increase the cognitive learning results of students in elementary school class IV. Keywords: Science at elementary school, Thematic approach, Experimental methods, Learning Outcome at Cognitive